Twelve-month outcomes following surgical repair of the Achilles tendon. Issue 10 (October 2016) - Fox, G.; Gabbe, B.J.; Richardson, M.; Oppy, A.; Page, R.; Edwards, E.R.; Hau, R.; Ekegren, C.L.
Abstract: Introduction: Incidence of Achilles tendon rupture (ATR) has increased over recent years, and debate regarding optimal management has been widely documented. Most papers have focused on surgical success, complications and short term region-specific outcomes. Inconsistent use of standardised outcome measures following surgical ATR repair has made it difficult to evaluate the impact of ATR on a patient's health status post-surgery, and to compare this to other injury types. This study aimed to report the frequency of surgical repairs of the Achilles tendon over a five-year period within an orthopaedic trauma registry, and to investigate return to work (RTW) status, health status and functional outcomes at 12 months post-surgical repair of the Achilles tendon. Methods: Two hundred and four adults registered by the Victorian Orthopaedic Trauma Outcomes Registry (VOTOR) who underwent surgical repair of the Achilles tendon between July 2009 and June 2014 were included in this prospective cohort study. The Extended Glasgow Outcome Scale (GOS-E), 3-level European Quality of Life 5 Dimension measure (EQ-5D-3L), and RTW status 12 months following surgical ATR repair were collected through structured telephone interviews conducted by trained interviewers. Results: At 12 months, 92% of patients were successfully followed up. Of those working prior to injury, 95% had returned to work. 42% of patients reported a full recovery on the GOS-E scale. The prevalence of problems on the EQ-5D-3L at 12 months was 0.5% for self-care, 11% for anxiety, 13% for mobility, 16% for activity, and 22% for pain. 16% of patients reported problems with more than one domain. The number of surgical repairs of the Achilles tendon within the VOTOR registry decreased by 68% over the five-year study period. Conclusions: Overall, patients recover well following surgical repair of the Achilles tendon. However, in this study, deficits in function persisted for over half of patients at 12 months post-injury. The decreased incidence of surgical Achilles tendon repair may reflect a change in practice at VOTOR hospitals whereby surgery may be becoming less favoured for initial ATR management.